Structural features of the vacuum condensates of iron alloyed with tungsten - Barmin, A. E.; Zubkov, A. I.; Il'inskii, A. I. (Institute for Single Crystals, 2012)
The initial structure and the composition of Fe–W films which were obtained by vacuum deposition were studied by the methods of transmission electron microscopy, x-ray diffraction, energy-dispersive x-ray spectroscopy and x-ray fluorescence analysis. It is shown that microalloying of iron with tungsten results in dispersion iron matrix grain structure. The inhomogeneous distribution of tungsten within each grain was discovered. The observed regularities are explained by the formation of grain boundary segregation of alloying component during binary vapors condensation.

Методами просвічуючої електронної мікроскопії, рентгенівської дифрактометрії, енергодисперсійної рентгенівської спектроскопії та спектрального рентгенівського флуоресцентного аналізу вивчена вихідна структура і склад плівок Fe-W, отриманих вакуумним осадженням. Показано, що мікролегування заліза вольфрамом призводить до диспергування зеренної структури залізної матриці. Виявлено неоднорідний розподіл вольфраму в межах кожного зерна. Спостережувані закономірності пояснюються формуванням зерногранічних сегрегацій легуючого компонента при конденсації двокомпонентного пара.
Структурні особливості вакуумних конденсатів заліза, легованих вольфрамом
Keywords: nanocrystalline materials; segregation; thermal stability; vacuum condensates; вакуумне осадження; склад плівок; вольфрам; зерногранічні сегрегації